2022
DOI: 10.1007/s12274-022-4350-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered micro/nanofibrous nonwovens for functional face mask filter

Abstract: The worldwide COVID-19 pandemic has led to an attention on the usage of personal protective face masks. However, the longevity and safety of the commercial face masks are limited due to the charge dissipation of the electret meltblown nonwovens, which are dominate in the face mask filters. Herein, we design a type of multi-layer structured nonwovens using meltblowing and electrospinning technologies. The complex nonwovens involving meltblown and electrospun fibers are designed to possess multilevel fiber diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Silver nanoparticles incorporated in PLA nonwoven face mask filters exhibited antibacterial activity up to 99.99% against E. coli while maintaining the pressure drop at 105 Pa and high filtration efficiency (99.1% for PM 0.3 ). 122 NanoLayr Ltd, a filter manufacturer in New Zealand has fabricated a three-layered face mask for which the middle layer is composed of electrospun PLA nanofibers and manuka triketone as the antimicrobial agent source, sandwiched between two outer layers of PLA spun-bonded non-woven fabric counterparts. 123 The PLA/manuka triketone filter media showed a virus reduction of 99%, 99.82% and 99.69% against influenza A, human coronavirus 229E and SARS-CoV-2 respectively after two hours of contact time, ≥98% filtration efficiency and pressure drop of 48–59 Pa (air velocities = 8 L min −1 ).…”
Section: Production Of Sustainable Face Mask Nonwovensmentioning
confidence: 99%
“…Silver nanoparticles incorporated in PLA nonwoven face mask filters exhibited antibacterial activity up to 99.99% against E. coli while maintaining the pressure drop at 105 Pa and high filtration efficiency (99.1% for PM 0.3 ). 122 NanoLayr Ltd, a filter manufacturer in New Zealand has fabricated a three-layered face mask for which the middle layer is composed of electrospun PLA nanofibers and manuka triketone as the antimicrobial agent source, sandwiched between two outer layers of PLA spun-bonded non-woven fabric counterparts. 123 The PLA/manuka triketone filter media showed a virus reduction of 99%, 99.82% and 99.69% against influenza A, human coronavirus 229E and SARS-CoV-2 respectively after two hours of contact time, ≥98% filtration efficiency and pressure drop of 48–59 Pa (air velocities = 8 L min −1 ).…”
Section: Production Of Sustainable Face Mask Nonwovensmentioning
confidence: 99%
“…where a higher capture of fine particles with size below 0.5 μm was attributed to the addition of electrospun nanofiber with smaller inter-fiber space on MB-based PE membrane, which was made instead of larger pores [ 160 ]. Furthermore, experimental evidence based on water vapor transmission rate (WVT) revealed that multilayer membranes based on electrospun and MB fabric provided higher values of WVT compared to that observed in commercial face masks, thus proving a better passage of moisture air during exhalation, and therefore a less human discomfort in wearing the mask [ 150 , 160 ] ( Fig. 6 k).…”
Section: The Use Of Electrospun Nanofibers In Surgical Mask and Respi...mentioning
confidence: 99%
“…However, there are still many drawbacks with pure electrospun membrane for air filtration, such as high cost, low dust holding capacity [ 20 , 21 ]. To overcome these drawbacks, a lot of research has been done such as surface structure design [ 22 ], fiber and pore size optimization [ 23 , 24 ] and fiber surface modification [ 25 ]. PVDF (Polyvinylidene fluoride) nano fibers were widely studied for energy harvesters and tactile sensors due to its piezoelectric property [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%